Simulation-Based Arduino Basic Electrical Monitoring System for Educational Applications - Siti Syafinah Ahmad Hassan; Nuril Azmi Muslimin; Fabian Halley Pata; Nadia Austin; Hushairi Zen (Journal of Electronic Voltage and Application, 2026)
This paper presents a fully simulation-based and low-cost electrical monitoring system for educational applications in embedded systems laboratories, developed entirely in Tinkercad using Arduino Uno simulation. The methodology employs Arduino Uno simulation in Tinkercad with a voltage divider circuit for input voltage measurement, potentiometer (connected to A0) for variable load conditions and LED brightness control, 16x2 LCD (D4-D11) for real-time display of input voltage, load voltage, power consumption and three LEDs (red, yellow, green) for load indication based on voltage thresholds, validated using Tinkercad's built-in multimeter. Results show accurate voltage and power monitoring with close agreement between LCD values and built-in multimeter readings, plus correct LED status responses (green for low load 5V). This project offers a fully virtual, accessible, and hands-on learning experience, helping students build foundational knowledge in electrical monitoring, circuit interfacing, and embedded programming using simulation-based tools.